Hydrangea ofeliae nom. nov. (Hydrangeaceae) from the Philippines - Sodusta, Patrick Jason A.; Lumawag, Benith Grace E. (Phytotaxa, 2019)
The most recent study on the molecular systematics of the Family Hydrangeaceae has shown that the genera Decumaria Linnaeus (1753: 397), Dichroa Loureiro (1790: 301), Broussaisia Gaudichaud (1830: 479), Schizophragma Siebold & Zuccarini in Siebold (1838: 58), Platycrater Siebold & Zuccarini in Siebold (1838: 62), Cardiandra Siebold & Zuccarini in Siebold (1839: 119), Pileostegia Hook.f. & Thomson (1857: 57) and Deinanthe Maximowicz (1867: 2) are congeneric with Hydrangea Linnaeus (1753: 397), so that the latter can be treated as monophyletic (De Smet et al. 2015). Following the results of this study, several new combinations were made including the species which can also be found in the Philippines, Dichroa febrifuga Loureiro (1790: 301) into Hydrangea febrifuga (Loureiro) Y.De Smet & Granados (2015: 750).